Participation and empowerment : determining the healthcare organization's success - Haidar RT; Ahmad Fareed AR; Jamsiah M (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Introduction : An organization performs well with proper management methods. Participation is a process involving cooperation and collaboration within all levels of individuals, groups or community for the purpose of organization improvement. Empowerment brings the organization further by delegation of power and responsibilities to others for better result. Methodology : This is a systematic review on various publications, articles and studies based on the findings and researches conducted by experts and scholars involved with participation and empowerment of organisations Results : Participation and empowerment are crucial in every organization including healthcare. Its success depends on factors such as proper planning, mutual understanding, regular training and continuous education. They contribute towards better outcome in goal setting, decision making, problem solving and organizational development. There are also various levels of empowerment and participation depending on the type of activities, organisation’s performance and level of authority. Conclusion : The prerequisite for an organisation’s success is dependent upon holistic participation and appropriate empowerment. The benefits gained from these measures are indeed invaluable. It creates sense of ownership, increases motivation and satisfaction, optimizing resources, promote innovations, enhancing quality and improving efficiency.